Tumor Microenvironment Responsive Key Nanomicelles for Effective Against Invasion and Metastasis in Ovarian Cancer Using Mice Model - Liu Y; Kong L; Yu Y; Zang J; Zhang L; Guo RB; Li ST; Cheng L; Li XT; Chen YQ (International Journal of Nanomedicine)
Yang Liu,1,2 Liang Kong,1,2 Yang Yu,1,2 Juan Zang,1,2 Lu Zhang,1,2 Rui-Bo Guo,1,2 Shu-Tong Li,1,2 Lan Cheng,1,2 Xue-Tao Li,1,2 You-Qiang Chen1,2 1School of Pharmacy, Liaoning University of Traditional Chinese Medicine, Dalian, 116600, People’s Republic of China; 2Shenyang Key Laboratory of Chinese Medicine Targeted Delivery Key Laboratory, Shenyang, 110847, People’s Republic of ChinaCorrespondence: Xue-Tao Li; You-Qiang Chen, School of Pharmacy, Liaoning University of Traditional Chinese Medicine, Shengming 1 Road 77, Double D Port, Dalian, 116600, People’s Republic of China, Tel +86411 8589 0170, Fax +86411 8589 0128, Email lixuetao1979@163.com; 89427765@qq.comBackground: Ovarian cancer is difficult to detect in its early stages, and it has a high potential for invasion and metastasis, along with a high rate of recurrence. These factors contribute to the poor prognosis and reduced survival times for patients with this disease. The effectiveness of conventional chemoradiotherapy remains limited. Nano-particles, as a novel drug delivery system, have significant potential for improving therapeutic efficacy and overcoming these challenges.Methods: According to the high expression level of matrix metalloproteinase-2 (MMP-2) in the tumor microenvironment, MMP-2 responsive nano-particles (PVGLIG-MTX-D/T-NMs) containing docetaxel and triptolide were prepared by the thin-film dispersion method. The synergistic effect between docetaxel and triptolide was systematically investigated, the ratio of the two drugs was optimized, and the physicochemical properties of the nano-particles and their ability to inhibit ovarian cancer cell growth and metastasis were evaluated in vitro and in vivo.Results: PVGLIG-MTX-D/T-NMs enhanced the targeting, stability, and bioavailability of the drug, while reducing the dose and toxicity. In addition, by regulating the expression levels of E-Cadherin, N-Cadherin, matrix metalloproteinases (MMPs), hypoxia-inducible factor 1-alpha (HIF-1α), and vascular endothelial growth factor (VEGF), it exhibited an inhibitory effect on epithelial-mesenchymal transformation (EMT) and tumor cell angiogenesis, and effectively inhibited the invasion and metastasis of ovarian cancer cells.Conclusion: PVGLIG-MTX-D/T-NMs achieved passive targeting of tumor sites by enhancing permeability and retention (EPR) effects. Subsequently, the uptake of the drug by tumor cells was enhanced by MMP-2 responsiveness and the modification of methotrexate targeting ligands. By regulating the expression levels of invasion- and metastasis-related proteins in tumor tissues, the nano-particles affected the EMT process, inhibited tumor angiogenesis, and suppressed the malignant potential of invasion and metastasis in ovarian cancer. These findings provided a new direction for further exploration of tumor-targeted therapy.Keywords: nano-drug delivery system, tumor microenvironment, docetaxel, triptolide, epithelial mesenchymal transition, angiogenesis